OPTIMASI HARGA PRODUK PULLEY PRIMARY SEPEDA MOTOR MATIC DENGAN PENDEKATAN SIMULASI COMPUTER AIDED MANUFACTURING BERDASARKAN MATERIAL YANG DIGUNAKAN DAN PENYESUAIAN SLOPE PRIMARY FIXED SHEAVE - Iqbal Fahreza (2020)
The development of manufacturing technology is very fast, making a nation to think ahead by realizing an advanced national life. Current technological advances are very influential from various aspects of life. At present the automatic transmission system, or better known as the Continuous Variable Transmission (CVT) system, has been developed in Indonesia. The pulley in the CVT transmission system is the most important component in the automatic motorcycle that is used to move the speed that is in accordance with the rotation of the engine automatically without using the transmission gear, but using the v-belt as a liaison or successor to the rotation that occurs in both pulleys. Based on observations made on automatic motorcycle users, there are a number of complaints felt by one of the non-responsive motorcycle automatic performance, it is very pronounced when traveling on steep terrain or hilly terrain. This aspect meets the needs of consumers who want to make changes to the primary pulley, there are many ways to do this, one of which is by making changes to the angle of the pulley. Changes in the angle of the pulley can be done by replacing aftermarket products that are quite expensive and not affordable. In this study the authors use the simulation software solidworks to process CAD / CAM, based on the above problems the research conducted by the author compares the production of aftermarket and pulley products 14⁰ and 13.5⁰ which is more optimal in terms of materials used, time and cost of using Computer Aided Manufacturing (CAM) simulation software. Computer Numerical Control (CNC) is the development of conventional machining tools combined with the help of computer control media in the form of a program so that the process can be done quickly, and accurately.